2016
DOI: 10.4172/2155-6113.1000587
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Inflammatory Protein-3 Alpha (MIP-3α)/CCL20 in HIV-1- Infected Individuals

Abstract: Objective Uncontrolled HIV infection progresses to the depletion of systemic and mucosal CD4 and AIDS. Early HIV infection may be associated with increases in the concentration of MIP-3α in the blood and gut fluids. MIP-3α/CCL20 is the only chemokine known to interact with CCR6 receptors which are expressed on immature dendritic cells and both effector and memory CD8+ and CD4+ T cells. The role and prognostic value of blood levels of MIP-3α in HIV-infected individuals has yet to be described. Methods We dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
1
8
1
Order By: Relevance
“…Lee et al and Baba et al suggested that CCL20 was upregulated during inflammation and elicited its effects on its target cells by binding to and activating the chemokine receptor CCR6 ( 69 , 70 ). During HIV infection, CCL20 has been shown to remain elevated throughout the course of the disease; the median CCL20 serum level was approximately 3.3-fold higher in HIV-infected individuals than in uninfected individuals and was negatively correlated with CD4 + T cell count ( 63 , 71 ).…”
Section: Chemokines and Chemokine Receptors Related To Hiv Replicatiomentioning
confidence: 99%
“…Lee et al and Baba et al suggested that CCL20 was upregulated during inflammation and elicited its effects on its target cells by binding to and activating the chemokine receptor CCR6 ( 69 , 70 ). During HIV infection, CCL20 has been shown to remain elevated throughout the course of the disease; the median CCL20 serum level was approximately 3.3-fold higher in HIV-infected individuals than in uninfected individuals and was negatively correlated with CD4 + T cell count ( 63 , 71 ).…”
Section: Chemokines and Chemokine Receptors Related To Hiv Replicatiomentioning
confidence: 99%
“…Higher levels of this cytotoxic defensin protein that is contained within neutrophil granules have been reported in IA tissue, suggesting that production of this protein may occur peripherally before neutrophils enter the IA wall [ 72 ]. Here the molecules CCR4 (which is a receptor of MIP-1 , RANTES , CCL17 , and MCP-1 ) [ 73 , 74 ] and CCR6 (which is a receptor of MIP-3α ) [ 75 ] were also related to the TNF node. We suspect that these receptors, which play a role in dendritic and T cell migration and recruitment during inflammation, [ 76 ] may coordinate inflammatory cell migration once expressed in aneurysm tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Though IL-6 production can be initiated by IL-1β induced transactivation of NF-κB, a single 24 hr N9 exposure may not be sufficient to significantly increase CVL secretion of IL-6, as previously reported by Fichorova and co-workers [18], which was in agreement with the results observed in the current study. Since the presence of IL-1β, IL-8, TNFα and MIP-3α can result in an influx and activation of HIV-susceptible cells at the vaginal mucosa including T cells [60], macrophages, and Langerhans cells [61], we further assessed the levels of these markers in different sections of the rabbit vagina. Similarly, N9-enhanced protein expression of these mediators in vaginal tissue were mitigated in the presence of HCQ (Fig.…”
Section: Discussionmentioning
confidence: 99%